Comparison of Antibody Repertoires against Staphylococcus aureus in Healthy Individuals and in Acutely Infected Patients - Dryla, Agnieszka (American Society for Microbiology, 2005)
The management of staphylococcal diseases is increasingly difficult with present medical approaches. Preventive and therapeutic vaccination is considered to be a promising alternative; however, little is known about immune correlates of protection and disease susceptibility. To better understand the immune recognition of Staphylococcus aureus by the human host, we studied the antistaphylococcal humoral responses in healthy people in comparison to those of patients with invasive diseases. In a series of enzyme-linked immunosorbent assay analyses performed using 19 recombinant staphylococcal cell surface and secreted proteins, we measured a wide range of antibody levels, finding a pronounced heterogeneity among individuals in both donor groups. The analysis revealed marked differences in the antibody repertoires of healthy individuals with or without S. aureus carriage, as well as in those of patients in the acute phase of infection. Most importantly, we identified antigenic proteins for which specific antibodies were missing or underrepresented in infected patients. In contrast to the well-described transient nature of disease-induced antistaphylococcal immune response, it was demonstrated that high-titer antistaphylococcal antibodies are stable for years in healthy individuals. In addition, we provide evidence obtained on the basis of opsonophagocytic and neutralizing activity in vitro assays that circulating antistaphylococcal serum antibodies in healthy donors are functional. In light of these data we suggest that proper serological analysis comparing the preexisting antibody repertoires of hospitalized patients with different outcomes for nosocomial staphylococcal infections could be extremely useful for the evaluation of candidate vaccine antigens in addition to protection data generated with animal models.